2021
DOI: 10.1101/2021.07.06.451402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomes of novel Myxococcota reveal severely curtailed machineries for predation and cellular differentiation

Abstract: Cultured Myxococcota are predominantly aerobic soil inhabitants, characterized by their highly coordinated predation and cellular differentiation capacities. Little is currently known regarding yet-uncultured Myxococcota from anaerobic, non-soil habitats. We analyzed genomes representing one novel order (o__JAFGXQ01) and one novel family (f__JAFGIB01) in the Myxococcota from an anoxic freshwater spring in Oklahoma, USA. Compared to their soil counterparts, anaerobic Myxococcota possess smaller genomes, and a s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
2
2
0
Order By: Relevance
“…Contemporary descendants of the microorganisms, which were exclusively discovered in CH1_17, were found to be highly metabolically exible organisms that could adapt to resource variability by using different electron donors and acceptors or being involved in syntrophic interactions. For example, Myxococcota from anoxic aquatic environments being a strict anaerobe are capable of using fermentation, nitrate reduction, and dissimilarity sulfate reduction for energy acquisition [71]. The current discovery of MAGs for Desulfobacterota and MBNT15 in deeper MP_16.9 sample are in line with the previously obtained data that obligately anaerobic taxa such as sulfate reducers and candidate lineage MBNT15 thrive in more stable deeper marine sediments [72].…”
Section: Identi Cation and Distribution Of Magssupporting
confidence: 85%
“…Contemporary descendants of the microorganisms, which were exclusively discovered in CH1_17, were found to be highly metabolically exible organisms that could adapt to resource variability by using different electron donors and acceptors or being involved in syntrophic interactions. For example, Myxococcota from anoxic aquatic environments being a strict anaerobe are capable of using fermentation, nitrate reduction, and dissimilarity sulfate reduction for energy acquisition [71]. The current discovery of MAGs for Desulfobacterota and MBNT15 in deeper MP_16.9 sample are in line with the previously obtained data that obligately anaerobic taxa such as sulfate reducers and candidate lineage MBNT15 thrive in more stable deeper marine sediments [72].…”
Section: Identi Cation and Distribution Of Magssupporting
confidence: 85%
“…BGCs in the PA fraction were expressed predominantly from MAGs affiliated with the Omnitrophota, Desulfobacterota, Planctomycetota, Myxococcota, and Gammaproteobacteria. Planctomycetota genomes have recently been reported to contain diverse biosynthetic potential 37 , while the Gammaproteobacteria and Myxococcota are prolific producers of secondary metabolites 30,38 . The majority of expressed BGCs in the PA fraction encoded terpenes, RiPPs, and non-ribosomal peptides.…”
Section: Distribution and Expression Of Secondary Metabolite Biosynth...mentioning
confidence: 99%
“…Myxococcota bacteria was found more abundant in the AF and RF systems relative to AG which could be attributed to the positive correlation of this phyla with increased N (Wu et al, 2021). Myxococcota have been detected in a wide range of environments in predominantly anaerobic habitats (Murphy et al, 2021), and we found the maximum abundance of this phyla under FD conditions. Bacteroidetes phyla have been reported to be living in the rhizosphere (Mhete et al, 2020) which might be the reason for their higher abundance in the RF and AF with extensive tree root systems as compared to AG.…”
Section: Microbial Diversity and Metagenomics Analysissupporting
confidence: 53%